Tape Stripping - Searching for Minimally Invasive Biomarkers in Atopic Dermatitis - Weronika Zysk; Magdalena Trzeciak (Mattioli1885, 2024)
Atopic dermatitis (AD) is nowadays entering a new era of more targeted treatments. However, to make personalized medicine, which we are currently striving for, a reality, a reliable set of validated biomarkers is needed. The most practical seem to be biomarkers that can be obtained easily and minimally invasively. Tape stripping (TS) is a method that provides such an opportunity. This review summarizes the potential biomarkers of AD identified by the minimally invasive TS method. Thymic stromal lymphopoietin (TSLP), interleukin (IL)-13, CC chemokine ligand 17 (CCL17)/thymus and activation-regulated chemokine (TARC) and stratum corneum (SC) lipids can be used as predictive biomarkers for AD occurrence. CCL17/TARC also holds great promise for being reliable biomarkers for AD severity as well as treatment response.Nitric oxide synthase 2 (NOS2)/inducible nitric oxide synthase (iNOS) which high expression is specific for psoriasis may be a good biomarker for differential diagnosis between psoriasis and AD in challenging clinical situations.AD children with food allergy (FA) have a unique endotype characterized by selectively altered expression of various molecules in the skin that can indicate FA coexistence. Unfortunately, although numerous potential biomarkers have been found, none of these candidates have been validated and implemented into routine clinical practice, which still separates us from the possibility of a precise approach to AD patients.